Exogenous dissolved organic matter redirects humic carbon fate at mineral interfaces through pre-contact molecular conditioning - Yu Li; Guangxu Mi; Jianghao Cheng; Meiling Zhang; Ying Liu; Shuang Ai; Fan Yang; Kui Cheng (Water Research, 2026)

A natural special-shaped MXene/bamboo evaporator with synergistic hydrothermal management for solar water purification - Jinhong He; Zongpei Zhang; Tianqing Shu; Weisheng Yang; Xiaoxu Ma; Jingren Ma; Meiling Chen; Fengshan Zhang; Guigan Fang; Huining Xiao; Jingquan Han (Desalination, 2026)

Zeolitic imidazolate framework enabled heat-resistant enzymatic biosensor for real-time and non-invasive detection of glucose - Qingwen Zhang; Meiling Yuan; Jingwen Chen; Ying Yang; Meng Lu; Chaoyue Cui; Xiaohu Liu; Hu Chen; Yi Wang (Chemical Engineering Journal, 2026)

Genome-wide characterization of terpene synthase genes in Ginkgo biloba and their regulatory role in terpene trilactones biosynthesis - Ang Xu; Chenglin Luo; Chunxia Chen; Yumeng Gao; Wenjing Qin; Qi Wang; Lisha Shi; Xiaoming Yang; Meiling Ming; Fuliang Cao; Fangfang Fu (Plant Science, 2026)

Artificial humic acid reshapes microbial C-N metabolism and nitrogen partition in microplastic-contaminated soils - Qihe Gao; Shuang Ai; Meiling Zhang; Yu Li; Yantong Li; Yadong Ma; Jiale Zhang; Fan Yang; Kui Cheng (Journal of Hazardous Materials, 2026)

Sophoraflavanone G disrupts human sperm function via impairing CatSper-mediated Ca2+ signaling - Meiling Yang; Ze Xu; Jiali Zhang; Nanxi Ji; Jieling Huang; Yiling Lu; Chunli Sha; Sijie Gaoliu; Xuhui Zeng; Hang Kang; Liping Chen (Reproductive Toxicology, 2026)

TRPV4/IP3R-1-mediated endothelial pyroptosis drives pulmonary microvascular endothelial permeability in endotoxin-induced acute lung injury - Shasha Liu; Shuan Dong; Lirong Gong; Jing Yang; Huayang Liu; Meiling Piao; Ya Wu; Huirong An; Li Zhang; Jianbo Yu (Inflammation Research, 2026)

Spatiotemporal cube for identifying Cd-dominated heavy metal stress in rice using signal decomposition and hotspot analysis from GF-6 time series images - Yanan Wen; Tianyi Wang; Meiling Liu; Hui Zhang; Yuxin Zhao; Ben Yang; Xutao Yan; Ling Wu (International Journal of Remote Sensing, 2026)

Pseudomonas aeruginosa in Chinese mitten crab Eriocheir sinensis: Identification, pathogenic potential and control with Bdellovibrio powder - Li He; Yueqi Yang; Yiyao Liu; Meiling Liu; Haipeng Cao; Chunlei Gai; Weidong Ye (Journal of Invertebrate Pathology, 2026)

Linking molecular heterogeneity of artificial humic acid to divergent cadmium coordination behaviors - Yu Li; Xianghui Meng; Shuang Ai; Meiling Zhang; Guangxu Mi; Yurun Miao; Zhuqing Liu; Fan Yang; Kui Cheng (Journal of Hazardous Materials, 2026)

Bionic construction and performance assessment of 3D bioprinted small-diameter artificial blood vessels - Yuan-Zhu Xin; Wenyu Jin; Qianqian Wu; JunHee Lee; Geng Li; Yan Chen; Jun Liu; Seok-Jo Yang; Jiazi Gao; Meiling Quan; Zhenning Liu (Chemical Engineering Journal, 2026)

Bioinspired domed cone-pillar nanoarrays design for robust and low-haze-transparent superhydrophobic quartz glass - Yingying Dou; Yue Fan; Qiongwen Fu; Meiling Tao; Junyin Ouyang; Hongtao Liu; Lin Liu; Yabin Yang; Shilin Huang; Shan Zhou; Xuelin Tian (Chemical Engineering Journal, 2026)

Synergistic atomic-level anchoring and pore engineering of cobalt-nitrogen-carbon for anti-fouling and robust capacitive deionization - Huakun Pan; Haodong Zhang; Xinxi Teng; Yang Fan; Yaming Wang; Lin Li; Guisong Zhang; Meiling Liu; Haiou Song; Aimin Li; Shupeng Zhang (Chemical Engineering Journal, 2026)

Seamless 1-km hourly land surface temperature estimation via multi-source data integration and automated machine learning - Yumin Li; Meiling Gao; Zhenhong Li; Penghai Wu; Bin Wang; Rongtang Xu; Guijun Yang (Urban Climate, 2026)

Genome-wide analysis of the papaya bZIP gene family identifies CpbZIP52 as a key regulator of fruit postharvest ripening - Meiling Ding; Shanni Cao; Meng Zeng; Min Zhang; Hongya Tang; Xiaochun Chen; Xianqi Fu; Sicheng Bai; Min Yang; Kaidong Liu (Plant Science, 2026)

Effects of nodule geometry on collection performance and structural improvement of a rotary-rake collector for deep-sea mining - Qiang Yang; Zekun Chen; Junlan Deng; Meiling Liu; Jianxin Xia; Dingbang Wei (Ocean Engineering, 2026)

Synergy of interfacial modification and sustained release in plant-derived nanoliposomes for enhanced pesticide efficacy and dose reduction - Zhongxiang Zhao; Xipeng Jiang; Meiling Yang; Juan Yang; Shujie Ma; Lili Dong; Fengyue Suo; Jingao Dong; Lihui Zhang (Journal of Environmental Chemical Engineering, 2026)

Study on the removal effect of Enteromorpha polysaccharide on heavy metal-organic composite pollution - Xue Shen; Yingqiang Li; Meiling Li; Yaru Zai; Xue Han; Shida Zhang; Jin Wang; Zhigang Yang; Yang Song (Journal of Environmental Chemical Engineering, 2026)

Facet and crystallinity-dependent transformation of lepidocrocite impacts cadmium redistribution - Meiling Yin; Jin Wang; Songxiong Zhong; Xiaofei Li; Fei Huang; Chen Yang; Fangbai Li; Zhi Dang; Chuling Guo (Environmental Pollution, 2026)

Zwitterionic polyurethane-based solid polymer electrolytes for high-performance solid-state Lithium metal batteries - Jiaxing Liu; Bei Deng; Meiling Liu; Yaxue Zhang; Zhihao Yang; Tieqi Huang; Hongtao Liu (Chemical Engineering Journal, 2026)

Drug-Induced Noninfectious Myocarditis/Pericarditis: A Real-World Pharmacovigilance Study Using the FAERS Database - Shijie Zhao; Weiyi Chen; Chao Tao; Ke Wang; Liuxuan Yang; Ruixiao Li; Meiling Zhou; Jinlu Shang; Xianbin Liu (Cardiovascular Toxicology, 2026)

Hydrangea-derived nitrogen-doped carbon dots: A dual-purpose platform for on-site chlortetracycline detection and time-limited anti-counterfeiting - Meiling Long; Decheng Peng; Jun Yang; Shaogui Wu (Analytica Chimica Acta, 2026)

Global distribution of the terrestrial moisture dynamics response to the meteorological dry-wet abrupt alternation - Jianyu Fu; Mingzhu Cao; Yang Lu; Chunzhu Wei; Xuejin Tan; Meiling Zheng; Liqian Peng; Wenhao Jia; Bingjun Liu (Journal of Hydrology, 2026)

Exogenous plant growth-promoting rhizobacteria boosting photosynthetic efficiency via thylakoid lipid restructuring in potato under low-potassium conditions - Xin Zhou; Xin Cheng; Baoyu Fu; Meiling Li; Chao Luo; Haoyang Gong; Hongkun Yang; Jingye Fu; Chengcheng Cai; Kaiqin Zhang; Shunlin Zheng (Plant Science, 2026)

Singlet oxygen-dominated dual-pathways catalytic ozonation of sulfamethoxazole over FeOx-N-BC/O3–MNBs system - Meiling Cai; Xiaojun Miao; Xiaoyan Wang; Xueyan Xue; Hui Zhu; Liping Yang; Xinqian Zhang; Jiao Yin (Journal of Environmental Chemical Engineering, 2026)

Community characteristics and risks of disinfection residual bacteria (DRB) during intermittent chlorination of stored rainwater - Zhiwen Chen; Xiaobin Liao; Binxiong Hu; Ye Yang; Meiling Liu; Yingying Dong; Tao Li; Likun Lv; Mawuli Dzakpasu; Yuefeng Xie; Wendong Wang (Journal of Environmental Chemical Engineering, 2026)

Enhanced electrocatalytic degradation of concentrated simulated metronidazole wastewater by MIL-101(FeCu)/graphite felt electrodes - Songshan Jiang; Fan Wu; Rui Wen; Lin Xu; Qian Zhong; Meiling Yang; Bai He; Huan Yi; Huan Pang (Chemical Engineering Journal, 2026)

Promotion kinetics and mechanism of bio-oil reforming via reduced Ce/Fe-based oxygen carrier - Meiling Yang; Wanxia Hu; Cuiping Wang; Zhihao Zheng (Biomass and Bioenergy, 2026)

Impact of mid-high-latitude Eurasian ISO on extreme hot days in the middle-lower reaches of the Yangtze River valley during boreal summer - Meiling Zhang; Shuangyan Yang; Zhiwei Zhu; Tim Li (Climate Dynamics, 2026)

Stability and Transport of Ferrihydrite Nanoparticles in Alkaline Soils - Yan Gong; Meiling Wang; Shuting Tian; Qingwei Ding; Xia Li; Gaiqiang Yang; Qi Liu; Juanfang Yang; Lijuan Huo (Water, Air, & Soil Pollution, 2026)

Alleviating Clostridium perfringens-Induced Gut Lesionsin Broiler Chickens by Orally Administered Bovine Intestinal Alkaline Phosphatase - Wangli Ji; Daoxin Yang; Wenjing Zhang; Yuan Wang; Zhenzhen Hao; Kairui Guo; Xianhua Sun; Shuai Wang; Shuyan Yang; Jianshuang Ma; Huiying Luo; Bin Yao; et al. (Probiotics and Antimicrobial Proteins, 2026)

Research on high-resolution PM2.5 concentration estimation methods based on transfer learning - Meiling Xing; Bo Li; Wenhao Zhang; Guohong Li; Xiufeng Yang; Qiyue Liu; Qichao Zhao (Advances in Space Research, 2026)

Metagenomic and metatranscriptomic characterization of syntrophic propionate- and butyrate-oxidizing bacterial communities in Qiangyong proglacial lake sediments on the Qinghai-Tibet Plateau - Rong Wen; Hongfei Chi; Meiling Feng; Yang Zhao; Chengfang Ma; Keshao Liu; Qi Yan; Pengfei Liu (Soil Ecology Letters, 2026)

Cationic polyacrylamide (CPAM) assisted leaching of rare earth ore containing clay minerals by inhibiting swelling and promoting permeation of ammonium sulfate solution - Meiling Jiang; Huifang Yang; Wenqian Cui; Yunbo Yang; Zhenyue Zhang; Zhengyan He; Zhigao Xu; Ming Wu; Jun Zhao; Ruan Chi (Hydrometallurgy, 2026)

Disentangling adaptive strategies of eukaryotic phytoplankton to environmental stressors in the sediment-laden Yellow River: A multi-method perspective from eDNA and morphology - Meiling Yi; Shuang Xu; Feilong Li; Bowen Gao; Yang Li (Environmental Research, 2026)

Optimal information transmission in a non-Markovian auto-regulatory gene expression system - Zihao Wang; Meiling Chen; Zhenquan Zhang; Xiyan Yang; Tianshou Zhou; Changhong Shi; Jiajun Zhang (BioSystems, 2026)

Tetrahydrocurcumin for Major Depressive Disorder with Therapeutic Potential and Mechanistic Insights from Clinical and Preclinical Studies - Ying Guo; Jianping Xie; Haiyun Luo; Yun Yuan; Fang Long; Jingyuan Meng; Hui Tan; Yuanping Li; Bibo Cai; Meiling Chen; Liyan Yang; Jingmei Zhong; et al. (Molecular Neurobiology, 2026)

Solar-driven superhydrophobic modified polyurethane sponge for rapid in-situ recovery of oil and microplastics in marine oil spill co-contamination - Chuanliang Zhao; Sidan Peng; Bo Wu; Le Kang; Lanlan Liang; Meiling Liu; Liwei Yang; Wendong Wang; Xing Xu (Journal of Hazardous Materials, 2025)

Application of soda residue based material in a vertical flow constructed wetland for the simultaneous removal of tetracycline and phosphorus from freshwater aquaculture effluent - Ye Yang; Binxiong Hu; Tao Li; Meiling Liu; Ahmed Omer Abdalrahim Mohamed; Yingying Dong; Mawuli Dzakpasu; Hang Li; Yingyue Wang; Wendong Wang (Journal of Environmental Chemical Engineering, 2025)

Manufacture of a fluorescent covalent organic framework and its Eu3 + -functionalized material for the design of dual-functional platforms for fluorescent and colorimetric sensing - Yuqiang Xiao; Jiaqi Hu; Mingyue Wang; Yue Lan; Dandan Wang; Famin Ke; Lingling Li; Minmin Wang; Leijiao Peng; Meiling Yang; Tianzhen Gao; Jianming Wu; et al. (Journal of Environmental Chemical Engineering, 2025)

Integrating network pharmacology, molecular docking, and bioinformatics to explore the mechanism of sparganii rhizoma in the treatment of laryngeal cancer - Meiling Zheng; Rui Zhang; Xinxing Yang; Feiyan Wang; Xiaodi Guo; Long Li; Jin Wang; Yajun Shi; Shan Miao; Wei Quan; Shanbo Ma; Xiaopeng Shi (Molecular Diversity, 2025)

A novel “WRF+AutoML” framework for enhanced heat estimation in urban environments - Meiling Gao; Huifang Li; Fei Chen; Mengzi Zhou; Guijun Yang; Dun Zhu; Dawei Han; Zhenhong Li (Sustainable Cities and Society, 2025)

Long-term nitrogen enrichment affects soil organic carbon fractions through microbial pathways in fluvo-aquic soil - Binggeng YANG; Jiwen CUI; Meiling ZHANG; Kangrui FANG; Chao AI; Tengfei GUO; Shaomin HUANG; Dali SONG; Wei ZHOU (Pedosphere, 2025)

One stone, several birds: A carboxyl-carbazole-rich fluorescent covalent organic framework for the detection of tetrabromobisphenol S, Fe³ ⁺, ascorbic acid, D/L-arginine, and the removal of tetrabromobisphenol S - Jiaqi Hu; Mingyue Wang; Min Wang; Dandan Wang; Yuqiang Xiao; Yue Lan; Lingling Li; Meiling Yang; Minmin Wang; Leijiao Peng; Famin Ke; Xiurong Guo; et al. (Journal of Hazardous Materials, 2025)

Possible influences of tropical vegetation shift on the glacial-interglacial temperature changes - Liping Tian; Cong Chen; Mengyuan Wang; Chuanxiu Luo; Xiao Zhang; Yanming Ruan; Jiantao Cao; Meiling Man; Zhuo Zheng; Xiaoqiang Yang; Kangyou Huang; Li Li; et al. (Global and Planetary Change, 2025)

2,2',4,4'-tetrabromodiphenyl ether (BDE-47) induces early hearing loss in guinea pigs via activating AhR to trigger mitochondrial and endoplasmic reticulum stress-regulated autophagy - Jie Tang; Li Zhang; Yujia Yang; Chunji Wang; Fang Zhang; Muxin Yu; Nenghua Zhang; Guangtao Xu; Bo Hu; Meiling Shi; Long Xu (Archives of Toxicology, 2025)

Wheat yield prediction using an enhanced WOFOST with soil stratified hydrothermal module driven by GLASS and ERA5-land products over Yellow River Basin - Jing Zhang; Guijun Yang; Meiling Gao; Lijie Zhang; Weinan Chen; Miao Liu; Youming Zhang; Aohua Tang; Zhenhong Li (Computers and Electronics in Agriculture, 2025)

CO2 adsorption and separation properties of decorative paper impregnated with amino-functionalized cellulose nanofibers/waterborne acrylic resin - Xiaopin Bu; Qian Wei; Zhuoxin Liao; Yuding Zhu; Meiling Chen; Junhui Yang; Xiuzhen Lin; Donggyun Kim; Xiangyu Wang; Song Li; Jeonghun Kim; Wenkai Zhu (Chemical Engineering Journal, 2025)

CBT-Cys click ligation coupled with pregnancy test strips for nucleic acid assay - Meiling Zhang; Jiahang Song; Huawen Zhang; Yang Li; Xu Hun (Analytica Chimica Acta, 2025)

Achieving ultralong-lived flexible room-temperature phosphorescence, detection of strain and photostability, and high-level data encryption based on benzophenone derivatives - Yang Zhu; Haoqun Wu; Meiling Pan; Lei Ma; Yongtao Wang (Chemical Engineering Journal, 2025)

Environmental Impacts and Behaviors of Chromium in Pakchoi-Soil Systems Under Ambient and Elevated CO2 Levels - Yuning Wang; Yatu Huang; Ye Ding; Wentao Yang; Yabo Wang; Qiao Xu; Yao Yao; Xiaozhi Wang; Meiling Xu (Water, Air, & Soil Pollution, 2025)

Different responses of cyanobacterial communities to climate change and anthropogenic activities revealed by the 500-year sedimentary record of Lake Daihai - Jing Wang; Hai Xu; Jianghu Lan; Kang’en Zhou; Yunping Song; Jin Zhang; Meiling Yang; Baoli Wang (Anthropocene, 2025)

Large-scale mapping and uncertainty assessment of dominant tree species in southern China based on Sentinel-2 time series - Ben Yang; Yuxin Zhao; Junji Li; Meiling Liu; Lei Feng; Botian Zhou; Ling Wu (Journal of Environmental Management, 2025)

The high economic cost of biological invasions in China - Yuanyi Li; Jinyu Zhang; Jun Zhang; Jiacong Du; Ruxiang Yang; Meiling Niu; Yiming Li (Journal of Environmental Management, 2025)

Reorganization of antecedent rivers in response to the evolving landscape at the northeastern margin of the Tibetan Plateau - Baotian Pan; Zijuan Dong; Zhenbo Hu; David Bridgland; Qinhong Mo; Xiaohua Li; Menghao Li; Yanan Yang; Meiling Zhong; Renzhe Pan (Earth-Science Reviews, 2025)

The accumulation of microbial residues decreases with time after wetland-to-cropland conversion - Meiling Zhao; Guodong Wang; Yuanchun Zou; Lei Qin; Liang Yang; Ming Jiang (Applied Soil Ecology, 2025)

Neural-network-based adaptive control for space manipulator system with actuator faults: a fully actuated system approach - Meiling Hu; Xuebo Yang; Hanlin Dong; Yimu Jiang (Advances in Space Research, 2025)

Synergistic enhancement of ionic conductivity and mechanical strength of inorganic hydroxide exchange membranes via orientation engineering for water electrolysis - Qingjie Xi; Wei Wang; Ruixiang Guo; Chenyi Zhao; Xiaofen Liu; Xiaorui Jin; Yongan Yang; Kai-Ge Zhou; Meiling Wu (Chemical Engineering Journal, 2025)

Hypoxia-activated and status-reversing hydrogel platform initiates potent systemic immunity against triple-negative breast cancer - Zhike Li; Xianzhou Huang; Jin Yang; Meiling Shen; Yanjie You; Qinjie Wu; Changyang Gong (Chemical Engineering Journal, 2025)

Characteristics and mechanism of paclobutrazol degradation by the novel bacterial strain Kurthia gibsonii CGMCC 32305 - Wenxin Zhang; Meiling Shi; Yue Lou; Xinyi Liu; Xiaoli Dai; Yang Liu; Zhaoyu Li; Xu Su; Jiajia Li; YongQiang Tian (Journal of Environmental Chemical Engineering, 2025)

Divergent mitigation mechanisms of soil antibiotic resistance genes by biochar from different agricultural wastes - Yu Yao; Peiyang Yang; Bin Wang; Qiao Xu; Fanhao Song; Yabo Wang; Yingdong Zhao; Lei Guo; Xiaozhi Wang; Meiling Xu (Environmental Pollution, 2025)

Three in one: One host–guest doping system with mechanochromism, long afterglow, and thermally activated delayed fluorescence - Chao Yang; Meiling Pan; Lei Ma; Yongtao Wang (Chemical Engineering Journal, 2025)

Construction of site-specific immobilized lipase in bio-inspired “rigid and flexible” composite PVIm/ZIF-8 for long-cycle biodiesel synthesis from waste cooking oil - Qian Wang; Xinyuan Zheng; Meiling Ge; Rong Chen; Fangpei Ma; Jianming Pan; Fu Yang (Chemical Engineering Journal, 2025)

The design of novel lithium salt additives: 4-benzonitrile-1,3-double (trimethylboric acid) lithium (LBTA) to endow inherent superior stability in high voltage lithium ion batteries - Lucheng Li; Meiling Liu; Peng Yang; Wenfeng Yuan; Jun Chen (Chemical Engineering Journal, 2025)

Evolution of vegetation phenology and its response to urbanisation in Shaanxi province, China: A fine-scale perspective - Meiling Gao; Jingjing Ma; Zhenhong Li; Guijun Yang (Journal of Geographical Sciences, 2025)

Anemarrhenae rhizoma combined with Trichosanthis radix ameliorated type 2 diabetes in rats via the PI3K-Akt signalling pathway based on network pharmacology analysis - Yan Lin; Jinde Zheng; Xinyi Zhao; Bei Zheng; Ying Li; Wenjuan Yang; Bing Han; Hanxiao Tang; Meiling Zhang (Natural Product Research, 2025)

Estimation of winter wheat yield by assimilating MODIS LAI and VIC optimized soil moisture into the WOFOST model - Jing Zhang; Guijun Yang; Junhua Kang; Dongli Wu; Zhenhong Li; Weinan Chen; Meiling Gao; Yue Yang; Aohua Tang; Yang Meng; Zhihui Wang (European Journal of Agronomy, 2025)

Keystone taxa drive the synchronous production of methane and refractory dissolved organic matter in inland waters - Xinjie Shi; Wanzhu Li; Baoli Wang; Na Liu; Xia Liang; Meiling Yang; Cong-Qiang Liu (Water Research, 2025)

Advanced treatment of coal to ethylene glycol industry wastewater by catalytic ozonation: Performance and mechanism - Yingying Dong; Lan Yang; Nan Zhang; Ningning Xiao; Yongxia Sun; Ye Yang; Meiling Liu; Zhiwen Chen; Jiangwei Wang; Wendong Wang (Journal of Water Process Engineering, 2025)

The luminescence mechanism of two pure organic room temperature phosphorescent isomers, mechanical force detection, 3D modeling, and dynamic data encryption - Yang Zhu; Meiling Pan; Lei Ma; Yongtao Wang (Chemical Engineering Journal, 2025)

Effects of coexisting goethite or lepidocrocite on Fe(II)-induced ferrihydrite transformation pathways and Cd speciation - Meiling Yin; Xin Li; Chuling Guo; Qiaohui Zhong; Xiaofei Li; Lijuan Zeng; Yuting Zhou; Chen Yang; Zhi Dang (Science of The Total Environment, 2025)

Ultrastable Ti@Ir core-shell catalyst with low iridium loading for water electrolysis at industrial-level current density - Jiahao Yang; Zhaoping Shi; Yibo Wang; Hongxiang Wu; Jing Ni; Pengbo Wang; Meiling Xiao; Changpeng Liu; Wei Xing (Chemical Engineering Journal, 2025)

Expanding the electrochemical stable window of water through propylene carbonate addition for aqueous-based energy storage devices - Meiling Tang; Yu Meng; Yibing Yang; Shuilin Wu (Chemical Engineering Journal, 2025)

Longitudinal relationship between built environment and physical fitness in Chinese children and adolescents: Findings from the COHERENCE study - Jinghong Liang; Shan Huang; Wenwen Bao; Yingqi Pu; Meiling Liu; Xiuzhi Yang; Zhuowen Wu; Jiaqi Chen; Guanghui Dong; Yajun Chen (Building and Environment, 2025)

A mini-review on polyvinyl alcohol/lignin (nano)composites: Preparation, applications and perspectives - Meiling Han; Yu Zhang; Ying Zhang; Qing Ye; Mika Sillanpää; Xinli Zhu; Weijun Yang (Sustainable Chemistry and Pharmacy, 2024)

Functionalization of cellulose by facile Dissolution-Regeneration in A novel CS2/DBU/DMSO solvent system for detection of metal ions and antibacterial - Yuyan Zheng; Zinan Li; Meiling Chen; Jiyang Zuo; Tao Yang; Wenhua Miao; Yadong Zhao; Fei Liu; Jinggang Wang; Jin Zhu (Chemical Engineering Journal, 2024)

Comparative karyotype analysis provides cytogenetic evidence for the origin of sweetpotato - Jianying Sun; Qian Zhang; Meiling Xu; Mengxiao Yan; Xingyu Liu; Jian Sun; Qinghe Cao; Hongxia Wang; Jun Yang; Zongyun Li; Yonghua Han (Chromosome Research, 2024)

Genomic selection on ear height, plant height and grain yield in the primary testing stage of maize hybrids - Xinying Kong; Shuwen Ji; Yubo Liu; Xuecai Zhang; Meiling Liu; Chen Yue; Ruichen Yang; Cong Li; Xiaomei Dong; Ao Zhang; Yanye Ruan (Euphytica, 2024)

Microbial regulation on refractory dissolved organic matter in inland waters - Wanzhu Li; Baoli Wang; Na Liu; Xinjie Shi; Meiling Yang; Cong-Qiang Liu (Water Research, 2024)

Synergistic enhancement of cadmium immobilization and soil fertility through biochar and artificial humic acid-assisted microbial-induced calcium carbonate precipitation - Yu Li; Meiling Zhang; Xiaobin Wang; Shuang Ai; Xianghui Meng; Zhuqing Liu; Fan Yang; Kui Cheng (Journal of Hazardous Materials, 2024)

The coupling between tectonic uplift and climate change recorded by the Yellow River terraces during the Zoige basin excavation in the northeastern Tibetan Plateau - Qinhong Mo; Zhenbo Hu; David Bridgland; Menghao Li; Baotian Pan; Ningyi Li; Zijuan Dong; Xiaohua Li; Yanan Yang; Meiling Zhong; Renzhe Pan; Rob Westaway (Geomorphology, 2024)

Phosphorylation of RasGRP1 by Shc3 prevents RasGRP1 degradation and contributes to Ras/c-Jun activation in hepatocellular carcinoma - Xinran Zhang; Yun Liu; Rui Yang; Yuanyuan Guo; Meiling Yan; Ying Xiao; Yunzhuo Dong; Ruixia Zhang; Yinpeng Qin; Yishan Bu; Yi Zhang; Huier Gao (Molecular and Cellular Biochemistry, 2024)

Spatiotemporal variations of plankton communities in different water bodies of the Yellow River: Structural characteristics, biogeographic patterns, environmental responses, and community assembly - Meiling Yi; Lingqi Li; Haoran Li; Chang Liu; Ya Deng; Zi Wu; Yang Li (Journal of Hydrology, 2024)

Effects of microplastics on sedimentary greenhouse gas emissions and underlying microbiome-mediated mechanisms: A comparison of sediments from distinct altitudes - Meiling Yi; Jingnan Liu; Maosen Ma; Sibo Zhang; Xin Chen; Xinghui Xia; Yang Li (Journal of Hazardous Materials, 2024)

Identification and functional characterization of interleukin-22 (IL-22) in orange-spotted grouper (Epinephelus coioides) - Dapeng Yu; Guanjian Yang; Jingyi Mo; Meiling Zhang; Hongli Xia; Zhen Gan; Yishan Lu (Fish & Shellfish Immunology, 2024)

Histological and single-nucleus transcriptome analyses reveal the specialized functions of ligular sclerenchyma cells and key regulators of leaf angle in maize - Qibin Wang; Qiuyue Guo; Qingbiao Shi; Hengjia Yang; Meiling Liu; Yani Niu; Shuxuan Quan; Di Xu; Xiaofeng Chen; Laiyi Li; Wenchang Xu; Fanying Kong; et al. (Molecular Plant, 2024)

Novel superhydrophobic sponge with flower-like architecture for oily emulsion separation and organic pollutants photodegradation - Jinyue Yang; Zhanjian Liu; Jing Jing; Xiguang Zhang; Yuxin Fu; Meiling Li; Huaiyuan Wang (Journal of Environmental Chemical Engineering, 2024)

Validation of endogenous U6 promoters for expanding the CRISPR toolbox in Nicotiana tabacum - Pan Luo; Siyuan Li; Lulu Li; Yanyan Li; Ying Qiao; Xianzhi Wu; Meiling Wu; Zhihao Song; Yong Yang; Ji Feng; Xingchun Tang (In Vitro Cellular & Developmental Biology - Plant, 2024)

Farmland transfer contract performance and green production technology adoption among farmers: evidence from a survey of four provinces in China - Meiling Cui; Yang Guo; Yueqing Ji (Environmental Science and Pollution Research, 2024)

STAT2 negatively regulates RIG-I in the antiviral innate immunity of black carp - Ji Liu; Chushan Dai; Lijun Yin; Xiao Yang; Jun Yan; Meiling Liu; Hui Wu; Jun Xiao; Weiguang Kong; Zhen Xu; Hao Feng (Fish & Shellfish Immunology, 2024)

Resting-state EEG Microstate Features Can Quantitatively Predict Autistic Traits in Typically Developing Individuals - Huibin Jia; Xiangci Wu; Xiaolin Zhang; Meiling Guo; Chunying Yang; Enguo Wang (Brain Topography, 2024)

Pt,P-codoped carbon nitride nanoenzymes for fluorescence and colorimetric dual-mode detection of cholesterol - Meiling Chen; Yang Yang; Qinhua Chen; Lina Tang; Junlin Liu; Yujie Sun; Qiming Liu; Yulin Zhang; Guo-jun Zhang; Shaowei Chen (Analytica Chimica Acta, 2024)

In situ hydrodeoxygenation of heavy bio-oil using a Ce/Fe-based oxygen carrier in methanol-zero valent aluminum media - Meiling Yang; Guozhang Chang; Weiwei Cui; Peng Ni; Qiujie Yi; Laishun Yang; Cuiping Wang (Chemosphere, 2024)

Minocycline attenuates the bilirubin-induced developmental neurotoxicity through the regulation of innate immunity and oxidative stress in zebrafish embryos - Guanghua Xiong; Tianle Hu; Yihong Yang; Haiyan Zhang; Meiling Han; Jiahao Wang; Yipeng Jing; Hongbo Liu; Xinjun Liao; Yong Liu (Toxicology and Applied Pharmacology, 2024)

Stepwise degradation of organic matters driven by microbial interactions in China΄s coastal wetlands: Evidence from carbon isotope analysis - Meiling Yang; Na Liu; Baoli Wang; Yajun Li; Wanzhu Li; Xinjie Shi; Xinrui Yue; Cong-Qiang Liu (Water Research, 2024)

Isolation, heterologous expression, and functional determination of an iron regulated transporter (IRT) gene involved in Fe2+ transport and tolerance to Fe2+ deficiency in Vitis vinifera - Zhizhong Song; Xue Wang; Mengyuan Li; Youzheng Ning; Shengpeng Shi; Guangrong Yang; Hongxia Zhang; Meiling Tang; Bin Peng (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)
In plants, iron (Fe) regulated transporters (IRT) play important roles in uptake and transport of Fe that contributes to plant growth and development. However, biological functions of IRT transporters in fruit trees are still unknown. This study isolated 10 VvIRT genes from ‘Marselan’ grape, with varying expression levels across different tissues/organs, particularly enhanced under Fe depletion, especially in roots. Notably, VvIRT7 is the most abundantly expressed IRT gene in grape, beneficially restoring the Fe 2+ uptake defect of yeast mutant DEY1453. Furthermore, VvIRT7 showed dominant expression in the roots of irt1 /35S:: IRT7 complementation lines. Overexpressing of VvIRT7 rescued the retarded growth of irt1 knockout mutant, by increasing the fresh weight, dry weight, total root length, total root surface, lateral root numbers, total leaf chlorophyll, ACO activity, NiR activity, SDH activity, and tissue Fe concentration. This study provides insights for understanding molecular mechanisms of Fe uptake and transport in grape.

Migration and transformation of soil phosphorus by organic acids: a global meta-analysis - Ying Zhao; Meiling Zhang; Zhuqing Liu; Fan Yang (Journal of Soils and Sediments, 2024)

Evolution of sustainability and its driving characteristics in typical energy-rich counties in underdeveloped Northwest China - Honghua Li; Xingang Fan; Meiling Yang; Xueli Chen; Manman Zhao (Environment, Development and Sustainability, 2024)

A Fe-Ni-MOF-74@bamboo photothermal evaporator for efficient solar steam generation - Yiduo Chen; Dongxu Gu; Yujuan Zhao; Chaowei Zhang; Meiling Li; Qi Zhou; Yonghui Lin; Yaru Gong; Zhongmin Su; Weiting Yang (Desalination, 2024)

Scalable fabrication of a robust asymmetric superwetting Janus mesh by facile spray-coating for oil–water emulsions separation - Jing Jing; Zhanjian Liu; Xiguang Zhang; Jinyue Yang; Meiling Li; Ruixia Yuan; Guolin Jing; Huaiyuan Wang (Chemical Engineering Journal, 2023)

A halogen-free hyper-crosslinked ionic polymer for efficient multi-conversion of CO2 into carbonates under mild conditions, with a combination of theoretical study - Bowen Jiang; Jia Liu; Wenjie Xiong; Meiling Weng; Jigang An; Yuewei Fan; Leizhi Zheng; Guoqiang Yang; Zhibing Zhang (Chemical Engineering Journal, 2023)

Intrinsic photothermal phase change materials with enhanced toughness and flexibility for thermal management in extreme environments - Meiling Cui; Chong Tian; Yunyun Yang; Lei Huang; Qiang Liu; Na Yang; Fuqi Zhao; Xufu Cai; Weibo Kong (Chemical Engineering Journal, 2023)

Investigating the effects of organic amendments on soil microbial composition and its linkage to soil organic carbon: A global meta-analysis - Jiwen Cui; Binggeng Yang; Meiling Zhang; Dali Song; Xinpeng Xu; Chao Ai; Guoqing Liang; Wei Zhou (Science of The Total Environment, 2023)

Decomplexation of Ni-EDTA enhanced by Fe(III) reduction in the Fenton reaction: Insight into the role of carbonyl groups - Meiling Chen; Lin Ding; Shijun Zhu; Xiuqin Xiong; Xinkai Yuan; Yanhua Peng; Liming Yang; Hui Shi; Penghui Shao; Xubiao Luo (Journal of Environmental Chemical Engineering, 2023)

Development and evaluation of diffusive gradients in thin-films technique with a novel titanium peroxide binding gel for in situ measurement of Tl in natural waters and sediments - Hongmei Deng; Meiling Liu; Zhaodong Liu; Minhua Su; Yue Gao; Danxing Yang; Yuxuan Liu; Liang Ma; Zhiqiang Yu; Tangfu Xiao; Jun Luo (Journal of Hazardous Materials, 2023)

Savanna/rainforest dynamics and hydroclimate changes in northern boundary of tropical Asia over the past 150 kyrs - Cong Chen; Kangyou Huang; Zhuo Zheng; Yongqiang Zong; Peter Kershaw; Shixiong Yang; Liping Tian; Meiling Man; Sheng-Hua Li; Chris Brodie; Ning Wang; Xiao Zhang; et al. (Global and Planetary Change, 2023)

A novel perlucin-like protein (PLP) protects Litopenaeus vannamei against Vibrio harveyi infection - Jiamin Feng; Yongxiong Huang; Meiling Huang; Junliang Luo; Liwen Que; Shiping Yang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Decomplexation of Ni-EDTA by thermally activated persulfate: Efficiency and mechanism - Xinkai Yuan; Wei Xiong; Yanhua Peng; Bo Li; Jianzhi Zhang; Meiling Chen; Xiuqin Xiong; Liming Yang; Hui Shi; Xubiao Luo; Penghui Shao (Journal of Water Process Engineering, 2023)

Characterisation of kapok fibre's biochar for arsenate adsorption removal from aqueous solution. - Kanfolo Franck Herve Yeo; Yingying Dong; Tongxuan Xue; Zhiwen Chen; Nan Zhang; Ye Yang; Liu Han; Meiling Liu; Ange Nsilani Kouediatouka; Hanse Pablick Patherny Lobo Mouguegue; Wendong Wang (Environmental Research, 2023)

Atomically dispersed metal catalysts towards nitrogen reduction for Ammonia: From homogeneous to heterogeneous - Di Yang; Jinsheng Li; Meiling Xiao; Changpeng Liu; Wei Xing; Jianbing Zhu (Chemical Engineering Journal, 2023)

Light-driven uranyl-organic frameworks used as signal-enhanced photoelectrochemical sensors for monitoring anthrax - Guang Che; Weiting Yang; Cong Wang; Meiling Li; Xinyi Li; Yamin Fu; Qinhe Pan (Analytica Chimica Acta, 2023)

Channel migration in the northeastern margin of the Tibetan Plateau and its implication for fluvial response to the interaction between rapid tectonic activity, climatic fluctuation and human influence - Baotian Pan; Xiaohua Li; Zhenbo Hu; David Bridgland; Qinhong Mo; Zijuan Dong; Menghao Li; Yanan Yang; Rob Westaway; Guanghui Dong; Shanjia Zhang; Meiling Zhong (Quaternary Science Reviews, 2023)

Lacticaseibacillus casei LH23 Suppressed HPV Gene Expression and Inhibited Cervical Cancer Cells - Shiyue Hu; Yunpeng Hao; Xiao Zhang; Yaping Yang; Meiling Liu; Nan Wang; Tong-Cun Zhang; Hongpeng He (Probiotics and Antimicrobial Proteins, 2023)

Target and non-target analysis of organochlorine pesticides and their transformation products in an agrochemical-contaminated area - Di Huang; Lirong Gao; Shuai Zhu; Lin Qiao; Yang Liu; Qiaofeng Ai; Chi Xu; Wenwen Wang; Meiling Lu; Minghui Zheng (Chemosphere, 2023)

Terminal sliding-mode control for input-constrained free-float space manipulator via learning-based adaptive uncertainty rejection - Meiling Hu; Xuebo Yang; Hanlin Dong (Advances in Space Research, 2023)

A Quad-Functional On-demand released nanomissile achieves cascade amplification therapy of Triple-Negative breast cancer through reversing multiple resistance - Yan Wang; Xianzhou Huang; Shunyao Zhu; Lu Li; Jin Yang; Jie Li; Li Wang; Shuang Ma; Meiling Shen; Qinjie Wu; Changyang Gong (Chemical Engineering Journal, 2023)

Co-pyrolysis of heavy bio-oil and disposable masks pyrolysate with Ce/Fe-based oxygen carrier catalyst - Meiling Yang; Rongyang Zhao; Jianguang Qin; Jinyu Zhang; Laishun Yang; Cuiping Wang; Guangxi Yue (Fuel, 2023)

Self-intercepting interference of hydrogen-bond induced flexible hybrid film to facilitate lithium extraction - Meiling Wang; Tianyuan Zhang; Zhixiang Meng; Chongji Wang; Weikang Dong; Jijian Liu; Su Yang; Xudong Hou; Xiaoran Cheng; Weifeng Liu; Chenyang Xing; Xuguang Liu; et al. (Chemical Engineering Journal, 2023)

Rapamycin ameliorates brain damage and maintains mitochondrial dynamic balance in diabetic rats subjected to middle cerebral artery occlusion - Changchun Hei; Yujia Zhou; Chenyang Zhang; Furong Gao; Meiling Cao; Shilin Yuan; Yixin Qin; P. Andy Li; Xiao Yang (Metabolic Brain Disease, 2023)

Simultaneous determination of 13 paralytic shellfish toxins and tetrodotoxin in marine shellfish by porous graphitic carbon solid-phase extraction and hydrophilic interaction chromatography-tandem mass spectrometry - Peizhen Li; Rongmao Lu; Jie Zhu; Qingqing Ke; Dingnan Wang; Yang Wang; Chen Zhang; Xinyue Lu; Miaolong Zhao; Zhang Wang; Lingling Pan; Meiling Zhang; et al. (Food Additives & Contaminants: Part A, 2023)

Social capital and social integration after project-induced displacement and resettlement: Exploring the impact on three life stages in the Three Gorges Project - Yang Wang; Meiling Gao; Jian Zuo; Katharine Bartsch (The Social Science Journal, 2023)

A colloidal aqueous electrolyte modulated by oleic acid for durable zinc metal anode - Meiling Wang; Xiaoyu Wu; Di Yang; Hainan Zhao; Li He; Jiaran Su; Xu Zhang; Xiuxiu Yin; Kangning Zhao; Yizhan Wang; Yingjin Wei (Chemical Engineering Journal, 2023)

Correction to: Construction of HAnW‑based nanotwigs for removing inorganic fluorion in wastewater - Meiling Zhou; Hua Yang; Zejun Wang; Jiarui Ren; Rongmin Wang; Yufeng He (Environmental Science and Pollution Research, 2022)

Construction of HAnW-based nanotwigs for removing inorganic fluorion in wastewater - Meiling Zhou; Hua Yang; Zejun Wang; Jiarui Ren; Rongmin Wang; Yufeng He (Environmental Science and Pollution Research, 2022)

Research progress on antidiabetic activity of apigenin derivatives - Jingyi Jiang; Ting Tang; Yaling Peng; Meiling Liu; Qianwen Liu; Pengbing Mi; Zehua Yang; Hongfei Chen; Xing Zheng (Medicinal Chemistry Research, 2022)

Construction of WO3 nanocubes@Loess for rapid photocatalytic degradation of organics in wastewater under sunlight - Hua Yang; Peiyu Cao; Yaping Zhang; Meiling Zhou; Qianqian Wang; Rongmin Wang; Pengfei Song; Yufeng He (Environmental Science and Pollution Research, 2022)

Performance study of energy conversion system for ocean thermal profiler - Yanhu Chen; Bingzhe Chen; Meiling He; Luning Zhang; Qingchao Xia; Canjun Yang (Frontiers in Marine Science, 2022)
With the increasing scarcity of energy in the world, energy has become an important part of restricting the development and application of traditional ocean profilers. The method of converting ocean thermal energy (OTE) into electrical energy through an energy conversion system is a solution. The model establishment and performance analysis of the energy conversion system are the basis of the ocean thermal profiler (OTP) design. The model and performance are affected by the coupling of multiple parameters, especially rotational speed and pressure. In this study, a universal parameterized model for multi-parameter coupling was proposed. System performance analysis based on experiments including load current, speed, mechanical efficiency and total efficiency was presented. After model parameter identification, the error of mechanical efficiency was within 5%; the total efficiency error was less than 12.8%, and the maximum efficiency point error didn’t exceed 2.21%. The results indicated that the parameterized model was satisfactory for the engineering applications and could guide the design of OTP.

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Construction of mannose-modified polyethyleneimine-block-polycaprolactone cationic polymer micelles and its application in acute lung injury - Meiling Su; Heping Hu; Xuan Zhao; Chengyuan Huang; Bowen Yang; Zongning Yin (Drug Delivery and Translational Research, 2022)

Analyzing the micro-pore characteristics of tight oil reservoirs through the implementation of mercury intrusion technique - Meiling Jiang; Yunfeng Zhang; Yang Liu (Arabian Journal of Geosciences, 2021)

Dextran sulfate–modified pH-sensitive layered double hydroxide nanocomposites for treatment of rheumatoid arthritis - Xiahui Wang; Bowen Yang; Xiaowen Xu; Meiling Su; Mingrong Xi; Zongning Yin (Drug Delivery and Translational Research, 2021)

Pigment profile and gene analysis revealed the reasons of petal color difference of crabapples - Ting Shen; Meiling Han; Qianrui Liu; Chen Yang; Jiaxin Meng; Houhua Li (Brazilian Journal of Botany, 2021)

Study of the lower limit of pore throat filling in tight sandstone reservoir of Gaotaizi oil layer in Qijia area - Meiling Jiang; Yunfeng Zhang; Yang Liu (Arabian Journal of Geosciences, 2021)

Analysis of flavonoids and anthocyanin biosynthesis-related genes expression reveals the mechanism of petal color fading of Malus hupehensis (Rosaceae) - Meiling Han; Chen Yang; Jing Zhou; Jiabin Zhu; Jiaxin Meng; Ting Shen; Zhuanxia Xin; Houhua Li (Brazilian Journal of Botany, 2020)

Malus niedzwetzkyana (Dieck) Langenf transcriptome comparison and phylogenetic analysis with Malus sieversii (Ledeb) Roem - Meiling Yang; Shiyou Che; Yunxiu Zhang; Wenqin Song; Guorong Yan; Weiwei Yu (Genetic Resources and Crop Evolution, 2020)

Discovery and characterization of a stable lipase with preference toward long-chain fatty acids - Meiling Chen; Xiuzhen Gao; Wu Yang; Caili Sun; Junhuan Yang; Huaiyuan Zhang; Yuanda Song (Biotechnology Letters, 2020)

Two new monoterpene glucosides from Xanthium strumarium subsp. sibiricum with their anti-inflammatory activity - Hai Jiang; Xudong Xing; Meiling Yan; Xinyue Guo; Lin Yang; Liu Yang (Natural Product Research, 2019)

Universal stress protein in Malus sieversii confers enhanced drought tolerance - Meiling Yang; Shiyou Che; Yunxiu Zhang; Hongbin Wang; Tao Wei; Guorong Yan; Wenqin Song; Weiwei Yu (Journal of Plant Research, 2019)

Periodic Variation of AAK1 in an Aβ1–42-Induced Mouse Model of Alzheimer’s Disease - Xue Fu; Meiling Ke; Weihua Yu; Xia Wang; Qian Xiao; Min Gu; Yang Lü (Journal of Molecular Neuroscience, 2018)

Resveratrol promotes the embryonic development of vitrified mouse oocytes after in vitro fertilization - Yang Wang; Meiling Zhang; Zi-Jiang Chen; Yanzhi Du (In Vitro Cellular & Developmental Biology - Animal, 2018)

Latitudinal patterns and influencing factors of soil humic carbon fractions from tropical to temperate forests - Li Xu; Chunyan Wang; Jianxing Zhu; Yang Gao; Meiling Li; Yuliang Lv; Guirui Yu; Nianpeng He (Journal of Geographical Sciences, 2018)

Experimental wave attenuation study over flexible plants on a submerged slope - Zegao Yin; Xiaoyu Yang; Yuanzhao Xu; Meiling Ding; Haixiang Lu (Journal of Ocean University of China, 2017)

Identification and expression analysis of microRNAs during ovule development in rice (Oryza sativa) by deep sequencing - Ya Wu; Liyu Yang; Meiling Yu; Jianbo Wang (Plant Cell Reports, 2017)

Comparative genomic analysis of three white spot syndrome virus isolates of different virulence - Fang Li; Meiling Gao; Limei Xu; Feng Yang (Virus Genes, 2017)

Genome-wide transcriptome analysis of female-sterile rice ovule shed light on its abortive mechanism - Liyu Yang; Ya Wu; Meiling Yu; Bigang Mao; Bingran Zhao; Jianbo Wang (Planta, 2016)

Synergistic Anti-Cancer Effects of Icariin and Temozolomide in Glioblastoma - Lijuan Yang; Yuexun Wang; Hua Guo; Meiling Guo (Cell Biochemistry and Biophysics, 2015)

Is the Hypoglycemic Action of Vanadium Compounds Related to the Suppression of Feeding? - Meiling Huang; Yaling Wu; Na Wang; Ziwei Wang; Pan Zhao; Xiaoda Yang (Biological Trace Element Research, 2014)

Vanadyl acetylacetonate upregulates PPARγ and adiponectin expression in differentiated rat adipocytes - Yaling Wu; Meiling Huang; Pan Zhao; Xiaoda Yang (JBIC Journal of Biological Inorganic Chemistry, 2013)

Mining EST-Derived SSR Markers to Assess Genetic Diversity in Cassava (Manihot esculenta Crantz) - Meiling Zou; Zhiqiang Xia; Peng Ling; Yang Zhang; Xin Chen; Zusheng Wei; Weiping Bo; Wenquan Wang (Plant Molecular Biology Reporter, 2011)

Characterization and identification of Sox2+ radial glia cells derived from rat embryonic cerebral cortex - Haoming Li; Guohua Jin; Jianbing Qin; Meiling Tian; Jinhong Shi; Weiwei Yang; Xuefeng Tan; Xinhua Zhang; Linqing Zou (Histochemistry and Cell Biology, 2011)

Molecular characterization of the bacterial composition in two waste silk refining systems - Meiling Zhang; Xuexia Yang; Tian Zhang; Jun Chen; Di Xue (World Journal of Microbiology and Biotechnology, 2011)

Development of a real-time RT-PCR method for rapid detection of H9 avian influenza virus in the air - Jing Lv; Baozhi Wei; Tongjie Chai; Xianzhu Xia; Zengmin Miao; Meiling Yao; Yuwei Gao; Rong Huang; Huili Yang; Uwe Roesler (Archives of Virology, 2011)

Generation and identification of rat fetal cerebral radial glia-like cells in vitro - Haoming Li; Guohua Jin; Jianbing Qin; Meiling Tian; Xuefeng Tan; Xinhua Zhang; Weiwei Yang; Jinhong Shi; Linqing Zou (In Vitro Cellular & Developmental Biology - Animal, 2011)

Polymerase chain reaction analysis of laboratory generated bioaerosols - Zhai Junhui; Yang Ruifu; Che Fengxiang; Chen Meiling; Cui Hong (Aerobiologia, 1997)